Pengaruh Model Problem Based Learning Terhadap Hasil Belajar Siswa - Rohani, Rohani; Octavia, Erna; Nurfitriani, Nurfitriani (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2025)
This study aims to obtain objective information regarding the influence of the Problem-Based Learning (PBL) model on students' learning outcomes in the Civic Education subject for Class XID at SMAN 03 Sungai Kakap. This research employs the Experimental Method with a Pre-Experimental Design, specifically the One-Group Pretest-Posttest Design. Data collection techniques include Measurement, Direct Observation, and Document Study. The data collection instruments used consist of a learning outcome test designed to measure students' comprehension ability in Civic Education, as well as Observation Sheets and Documentation. The study population consists of 30 students from Class XID, comprising 16 female students and 14 male students. Data analysis was conducted using mean calculations, paired t-test, and t-test analysis. The results of this study, based on t-test calculations at a significance level of α = 0.005, show that t_calculated > t_table (11.408 > 1.699). Therefore, Ho is rejected and Ha is accepted, indicating that the Problem-Based Learning model has a significant effect on students' learning outcomes.